(untitled) (Хабаршы. Психология және социология сериясы, 2021)
This article presents some of the results of a sociological study regarding the role of teachers in the development of children and adolescents in Kazakhstan. The study was conducted by an independent research organization, the Center for Study of Public Opinion, it is a large-scale research project cover- ing all regions of Kazakhstan, urban and rural areas. An empirical study of children and adolescents aged 8-17 years was conducted using a survey. In turn, the object of the study was divided into two groups according to the age of 8-12 and 13-17 years. The results of the 2005 respondents survey showed that teachers play an important role in the upbringing of children, they cultivate responsibility and respect for each other in children. For children and adolescents, teachers form social and national identity and personality formation, carry out educational work. The results also show that school teachers are in sec- ond place after families in shaping the worldview of children. In addition to the educational function, teachers play a kind of role of protectors and advisers, as almost every fifth minor turns to teachers for help in solving their problematic issues. Key words: teachers, children and adolescences development, education, role of teachers, school and teachers, sociological survey